Electrical resistance changes of 3D carbon fiber/epoxy woven composites under short beam shear loading along different orientations. (15th November 2021) - Han, Chaofeng; Huang, Shuwei; Sun, Baozhong; Gu, Bohong
Highlights: Electro-mechanical behaviour of 3D woven composites along different directions was obtained. Electric resistance changes during cyclic shearing were measured. Relationship between electric resistance changes and inner damage was analyzed. Abstract: Electrical resistance under cyclic loading is important for designing intelligent structures of carbon-fiber reinforced composites. Here we report electrical resistance changes of 3D carbon fiber/epoxy woven composites under short beam shear loading along different orientations. The electric changes were measured in short beam shear tests combined with four-probe method and digital image correlation technology along five orientations, i.e., 0°, 30°, 45°, 60° and 90°. The on-axis (0° and 90°) samples have higher electrical conductivity, shear strength and resistance increase than other off-axis (30°, 45° and 60°) samples. Relative resistance changes become larger during monotonic loading and decrease under cyclic loading. The 45° and 60° samples show a higher relative resistance change compared with other samples under cyclic loading. Relationship between shear strength and relative resistance change was also revealed. This electric-mechanical coupling behavior provides a possible way for characterizing inner damages.